Neural PP attachment disambiguation systems - Do, Bich-Ngoc; Rehbein, Ines (Universität, 2023)
This resource contains code for different types of neural PP attachment disambiguation systems: A disambiguation system inspired by de Kok et al. (2017) but with the ranking loss function. A disambiguation system with biaffine attention similar to the neural dependency parser in Dozat and Manning (2017). The systems are described in details in the paper: Do and Rehbein (2020). "Parsers Know Best: German PP Attachment Revisited". We also include all pre-trained models reported in the paper.